Abundance drives broad patterns of generalisation in plant-hummingbird pollination networks - Simmons, Benno I; Vizentin-Bugoni, Jeferson; Maruyama, Pietro K; Cotton, Peter A; Marin-Gomez, Oscar H; Lara, Carlos; Lasprilla, Liliana R; Maglianesi, Maria A; Ortiz-Pulido, Raul; Rocca, Marcia A; Rodrigues, Licleia C; Tinoco, Boris; et al. (bioRxiv, 2018)
Abundant pollinators are often more generalised than rare pollinators. This could be because abundance drives generalisation: neutral effects suggest that more abundant species will be more generalised simply because they have more chance encounters with potential interaction partners. On the other hand, generalisation could drive abundance, as generalised species could have a competitive advantage over specialists, being able to exploit a wider range of resources and gain a more balanced nutrient intake. Determining the direction of the abundance-generalisation relationship is therefore a 'chicken-and-egg' dilemma. Here we determine the direction of the relationship between abundance and generalisation in plant-hummingbird pollination networks sampled from a variety of locations across the Americas. For the first time we resolve the direction of the abundance-generalisation relationship using independent data on animal abundance. We find evidence that hummingbird pollinators are generalised because they are abundant, and little evidence that hummingbirds are abundant because they are generalised. Additionally, a null model analysis suggests this pattern is due to neutral processes: most patterns of species-level abundance and generalisation were well explained by a null model that assumed interaction neutrality. These results suggest that neutral processes play a key role in driving broad patterns of generalisation in animal pollinators across large spatial scales.